Primary care physician eHealth profile and care coordination: a cross-sectional study - Mathieu Jendly; Valérie Santschi; Stefano Tancredi; Arnaud Chiolero (Swiss Medical Weekly)
BACKGROUND: Digital health holds promise for enhancing care coordination and supporting patient self-management. However, various barriers, including at the healthcare professional level, hinder its adoption. This cross-sectional study explored the eHealth profile of primary care physicians and its relationship with care coordination.